Proceedings. 16th IEEE VLSI Test Symposium (Cat. No.98TB100231)
DOI: 10.1109/vtest.1998.670893
|View full text |Cite
|
Sign up to set email alerts
|

A design for testability study on a high performance automatic gain control circuit

Abstract: A comprehensive testability study on a commercial automatic gain control circuit is presented which aims to identify design for testability (DfT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The results of testability analyses performed on representative analogue front-end components [28,31] and the interpretation of these for other high-speed architectures [32] provides evidence for superior test quality compared to conventional FFT-based testing. The kernel test time for the programmable gain block is reduced significantly while more time-consuming data capturing is avoided in A/D converter testing.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The results of testability analyses performed on representative analogue front-end components [28,31] and the interpretation of these for other high-speed architectures [32] provides evidence for superior test quality compared to conventional FFT-based testing. The kernel test time for the programmable gain block is reduced significantly while more time-consuming data capturing is avoided in A/D converter testing.…”
Section: Discussionmentioning
confidence: 96%
“…Further details and results are provided in [28]. To achieve good test quality, this part of the analogue front-end requires the assessment of gain step sizes and output voltage swing.…”
Section: Test Requirements Of High-speed Analogue Front-end Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…In this section a summary of the DfT study is provided, and further details can be found in [31]. The demonstrator is an AGC macro used to digitise sound signals.…”
Section: Detailed Dft Study On An Automatic Gain Control Circuit (Agc)mentioning
confidence: 99%
“…As a result of the detailed study of the AGC design [31], the DfT guidelines above have been proposed. Based on this knowledge, a new AGC design has been studied, similar to that presented in Figure 1 but with resistor ladder layout structure according to the above DfT rule.…”
Section: System Level Self Testmentioning
confidence: 99%